D-ARTNET22 V1: a neural network framework against stolen digital artworks getting Non-Fungible Token (NFT) labels - Dipro, Farhan Hasin; Simran, Sheikh Saif; Akhter, Mansura; Momo, Ramisa Fariha; Musharrat, Ramisa (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.